Un estudio sobre la respuesta estatal a la violencia de género - Zárate Mendoza, Angieluz Andrea (2022)
The purpose of this article is to publicize the work articulated between the Women’s Emergency Center and the Playa Rímac Police Station, in compliance with one of the Joint Action Protocols of Law No. 30364 to prevent, punish and eradicate violence against women. women and members of the family group. The Protocol in question becomes relevant since it involves a civil institution with a military-military one; also, because the National Police of Peru has the social stigma of being an institution that has shown various shortcomings in terms of the care and protection of women victims of gender violence. For this reason, it is important to highlight the situations of interaction between both services (CEM-CIA) to know the route that the victim travels when requesting help from a State institution. Part of the results of the investigation Critical Knots for the articulated attention of violence against women between the national police of Peru and the Women’s Emergency Centers will be shown. case: Commissioner Playa Rímac, 2019; The methodology used was of a qualitative nature, conducting interviews with the staff of the Commissioner and the Women’s Emergency Center.